2019
DOI: 10.1038/s41433-019-0469-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and risk factors for refractive error: a cross-sectional study in Han and Mongolian adults aged 40–80 years in Inner Mongolia, China

Abstract: Objectives To assess the prevalence of and risk factors for refractive error (RE) in Han and Mongolian adults aged 40-80 years in Inner Mongolia in China and to identify ethnic differences in RE between these populations. Methods Our cross-sectional study is part of the China National Health Survey (CNHS). The age-adjusted prevalence of RE in Han and Mongolian adults aged 40-80 in Inner Mongolia were compared. A multivariable logistic regression model was used to identify risk factors. Results Among 2090 peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 47 publications
5
14
1
Order By: Relevance
“…Pterygium is another risk factor of hyperopia in our study apart from age, which was also found in the study conducted by our team in Inner Mongolia and Yunnan (17,18). Eyes with hyperopia tend to have thinner cornea and sclera, but thicker conjunctiva, which might increase the risk of pterygium (44)(45)(46).…”
Section: Other Risk Factors Of Myopia and Hyperopiasupporting
confidence: 81%
See 4 more Smart Citations
“…Pterygium is another risk factor of hyperopia in our study apart from age, which was also found in the study conducted by our team in Inner Mongolia and Yunnan (17,18). Eyes with hyperopia tend to have thinner cornea and sclera, but thicker conjunctiva, which might increase the risk of pterygium (44)(45)(46).…”
Section: Other Risk Factors Of Myopia and Hyperopiasupporting
confidence: 81%
“…Shorter time length in rural area, higher education level, lighter active level and lower BMI are risk factors for myopia in our study. Similar study conducted by our team in Inner Mongolia of China also found that longer time length in rural area decrease the risk of myopia(p < 0.001) (17). A study in Beijing with 681 students showed a much lower risk of myopia in rural area compared to that under urban settings (OR 0.17, p < 0.001) (35).…”
Section: Other Risk Factors Of Myopia and Hyperopiasupporting
confidence: 71%
See 3 more Smart Citations